High-Precision Semiconductor Laser Current Drive and Temperature Control System Design - Yitao Zhao; Zengguo Tian; Xiangyu Feng; Zhengyuan Feng; Xuguang Zhu; Yiqun Zhou (Sensors, 2022)
To solve the problem in which the output power and wavelength of semiconductor lasers in fiber optic sensing systems are easily affected by the drive current and temperature, a high-precision current drive and temperature control system was developed in this study. The embedded system was used to provide a stable drive current for the semiconductor laser through closed-loop negative feedback control; moreover, some measures, such as linear slow-start, current-limiting protection, and electrostatic protection, were adopted to ensure the stability and safety of the laser’s operation. A mathematical model of the temperature control system was constructed using mechanism analysis, and model identification was completed using the M sequence and differential evolution (DE) algorithms. Finally, the control rules of the fuzzy proportional integral differentiation (PID) algorithm were optimized through system simulation to make it more suitable for the temperature control system designed in this research, and the accurate control of the working temperature of the semiconductor laser was realized. Experimental results showed that the system could achieve a linearly adjustable drive current in the range of 0–100 mA, with an output current accuracy of 0.01 mA and a temperature control accuracy of up to 0.005 °C.